2022
DOI: 10.26434/chemrxiv-2022-mtlwb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Formal Cross-Coupling of Amines and Carboxylic Acids to Form sp3–sp2 Carbon–Carbon Bonds

Abstract: Amines and carboxylic acids are abundant building blocks for synthesis that classically are united to form an amide bond. To access new pockets of chemical space we are interested in the development of complementary amine–acid coupling reactions. In particular, the formation of carbon–carbon bonds by formal deamination and decarboxylation would be an impactful addition to the synthesis toolbox. Here we report a formal cross coupling of alkyl amines and aryl carboxylic acids to form C(sp3)–C(sp2) bonds followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Phactor™ facilitates the discovery of new reactivity. Our lab is broadly interested in novel amine-acid coupling reactions 50,51,[53][54][55] and particularly amine-acid C-C coupling reactions 53,55 . As part of our studies, we have been exploring mild benzoic acid decarboxylation methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phactor™ facilitates the discovery of new reactivity. Our lab is broadly interested in novel amine-acid coupling reactions 50,51,[53][54][55] and particularly amine-acid C-C coupling reactions 53,55 . As part of our studies, we have been exploring mild benzoic acid decarboxylation methods.…”
Section: Resultsmentioning
confidence: 99%
“…To follow up on our initial report (ref. 55), the catalysts, four additives, four ligands, and two reductants were tested in Figure 4D, and it was found that 31 was afforded at 47% product/internal standard with NiCl2•glyme as the catalyst, 4,4'-di-tertbutyl-2,2-bipyridine as ligand, zinc as the reductant, and lithium perchlorate as an additive. After additional optimization, the reaction array in Figure 4E was run to test the reaction's scope.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanistic challenge to be solved is how to convert an aroyl electrophile to an aryl electrophile; if this could be overcome, coupling to a wide array of alkyl electrophiles should be possible (Scheme ). …”
mentioning
confidence: 99%